(untitled) (E Conference Zone, 2022)
This article is devoted to lingua-didactic principles and strategies of teaching foreign languages for ESP classes, especially for engineers. The study also analyzes how to use such principles in the non- linguistic classroom when delivering the classes and keys to use proper modern approaches. In the process of the research, it is described the advantage and the problems of these principles.